Gyrosigma peisonis var. major var. nov., a new variety of Gyrosigma peisonis (Bacillariophyta) from Lake Qinghai, China - Peng, Yumei; Rioual, Patrick; Jin, Zhangdong; Sterrenburg, Frithjof A. S. (Phytotaxa, 2016)
The morphology and ultrastructure of Gyrosigma peisonis var. major var. nov., a new variety of Gyrosigma peisonis found in Lake Qinghai (China), are described here on the basis of light and scanning electron microscopy. Most of the morphological features of this new variety are identical to those of the nominal variety Gyrosigma peisonis var. peisonis, but the variety major differs in its distinctly larger cell size and its higher value for the longitudinal/transverse stria density ratio, however. The seasonal variation of this taxon, which was investigated by a sediment-trap study is also discussed.